2007
DOI: 10.1136/oem.2007.033886
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risks for adenocarcinoma of the nasal cavity and paranasal sinuses in the German wood industry

Abstract: The authors found an elevated ADCN risk for exposure to inhalable wood dust above 3.5 mg/m(3). The rareness of the disease does not allow the exclusion of risk below that concentration. For pigment stains, there is evidence for an association of historical exposure with the development of ADCN in German wood workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
(13 reference statements)
0
15
0
4
Order By: Relevance
“…It has already been shown that wood dusts, particularly that from hardwoods, have a carcinogenic potential (HadWeld and Macbeth 1971;Kleinsasser and Schroeder 1988;Pesch et al 2008). The proportion of primary woodworking occupations is higher in other European studies (Leclerc et al 1994;Bimbi et al 2004) than ours.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…It has already been shown that wood dusts, particularly that from hardwoods, have a carcinogenic potential (HadWeld and Macbeth 1971;Kleinsasser and Schroeder 1988;Pesch et al 2008). The proportion of primary woodworking occupations is higher in other European studies (Leclerc et al 1994;Bimbi et al 2004) than ours.…”
Section: Discussionmentioning
confidence: 66%
“…However, it has been shown that patients suVering from adenocarcinoma working in a primary woodworking occupation had frequently additional contact with formaldehyde-containing chipboards, as well. Although there is virtually no valid technical data on formaldehyde exposure, an overall increased risk of adenocarcinoma through formaldehyde in the wood industry appears to be conceivable (Luce et al 2002;Pesch et al 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The epidemiological studies published by the IARC after 1995 have shown contradictory evidence on carcinogenicity and occupational exposure to wood dust 4,7–11. Several paradoxical findings have offered opportunities for new studies to recapitulate the plausible carcinogenicity with stronger evidence, such as a much greater risk by exposure to softwood dust suggested in northern Europe than in North America,12 the conflicting dose-response pattern (strong link between nasopharyngeal cancer with low intensity and a short-duration exposure),6,9 and the uncommon evidence in lung cancer 4,13.…”
Section: Introductionmentioning
confidence: 99%
“…This cancer is recognized as an occupational cancer. In fact, it is well confirmed today that sinonasal adenocarcinoma is highly correlated with duration and level (3.5 mg/m 3 ) of wood dust exposure [3,4]. As such, woodworkers have very high risks of nasal cancer (Standard Mortality Ratio: 310, 95% CI, 160-560) [5,6].…”
Section: Introductionmentioning
confidence: 99%